The Quijada from Los Arcos (Navarre) and their family seat - Pastor Abáigar, Víctor (Huarte de San Juan. Geografía e Historia, 2009)
This lineage of the Quijada family, or Quixadaas they usually signed their name, settled in LosArcos in the second half of the sixteenth century,having earlier lived the city of Alfaro in La Rioja, andbefore that in Tierra de Campos.To study this family tree is to follow the path of thehistory of the town of Los Arcos throughout the threecenturies that it was annexed to Castille. The malesubjects always held positions of power in the council,within the noble groups they had always belongedto. Since the first fruits of the parish were underthe patronage of the council, these men kept goodcount of all the works of art in the church, some ofwhich they had donated themselves. When he hadno direct male descendents, Luis Francisco Quixaday Arrese looked for an eligible nobleman for hisdaughter in Estella among the family of NavarroLadrón de Zegama y Amburz, and later in Elciegoamong the Saenz de Navarrete, with whom he gainedcontinuing social prestige into the twentiethcentury.
Keywords: Juan Quixada; Tierra de Campos; Chancillería de Valladolid Sala de Hijosdalgo; Parish patronage; Perpetual alderman